Energy law in Malaysia - Ansari, Abdul Haseeb (Kluwer Law International, 2011)
Derived from the renowned multi-volume International Encyclopaedia of Laws, this book provides a systematic approach to legislation and legal practice concerning energy resources and production in Malaysia. The book describes the administrative organization, regulatory framework, and relevant case law pertaining to the development, application, and use of such forms of energy as electricity, gas, petroleum, and coal, with attention as needed to the pervasive legal effects of competition law, environmental law, and tax law. A general introduction covers the geography of energy resources, sources and basic principles of energy law, and the relevant governmental institutions. Then follows a detailed description of specific legislation and regulation affecting such factors as documentation, undertakings, facilities, storage, pricing, procurement and sales, transportation, transmission, distribution, and supply of each form of energy. Case law, intergovernmental cooperation agreements, and interactions with environmental, tax, and competition law are explained. Its succinct yet scholarly nature, as well as the practical quality of the information it provides, make this book a valuable resource for energy sector policymakers and energy firm counsel handling cases affecting Malaysia. It will also be welcomed by researchers and academics for its contribution to the study of a complex field that today stands at the foreground of comparative law.